To find the product of the polynomial expressions \( (xy + 1)(x - 3) \), we'll use the distributive property (also known as the FOIL method for binomials).
Let's multiply each term in the first expression by each term in the second expression:
- \( xy \cdot x = x^2y \)
- \( xy \cdot (-3) = -3xy \)
- \( 1 \cdot x = x \)
- \( 1 \cdot (-3) = -3 \)
Now, combine these results: \[ x^2y - 3xy + x - 3 \]
So, the final product is: \[ x^2y - 3xy + x - 3 \]
Therefore, the correct response is: x²y − 3xy + x − 3